2015
DOI: 10.1093/jxb/erv321
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sulphur deprivation on osmotic potential components and nitrogen metabolism in oilseed rape leaves: identification of a new early indicator

Abstract: Identification of early sulphur (S) deficiency indicators is important for species such as Brassica napus, an S-demanding crop in which yield and the nutritional quality of seeds are negatively affected by S deficiency. Because S is mostly stored as SO4 (2-) in leaf cell vacuoles and can be mobilized during S deficiency, this study investigated the impact of S deprivation on leaf osmotic potential in order to identify compensation processes. Plants were exposed for 28 days to S or to chlorine deprivation in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…Total RNA was extracted from 200 mg of root and leaf fresh matter as previously described [36]. For RT, 1 μg of total RNA was converted to cDNA with an iScript cDNA synthesis kit according to the manufacturer’s protocol (Bio-Rad, Marne-la-Coquette, France).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was extracted from 200 mg of root and leaf fresh matter as previously described [36]. For RT, 1 μg of total RNA was converted to cDNA with an iScript cDNA synthesis kit according to the manufacturer’s protocol (Bio-Rad, Marne-la-Coquette, France).…”
Section: Methodsmentioning
confidence: 99%
“…For S-demanding crops such as oilseed rape, S deficiency provokes multiple plant physiological changes leading to losses in yield and seed quality through modified lipid and protein composition of seeds [30, 31, 32, 33, 34]. It has already been suggested that the analysis of plants rather than soil via total S, SO 4 2- or N:S, malate:sulfate or ([Cl - ]+[NO 3 - ]+[PO 4 3- ]):[SO 4 2- ] ratios could be used to detect plant S requirements (for review see [35, 36] but these parameters are affected by growth stage and growth rates or need laboratory analyses, making them unreliable as diagnostic indicators [35, 37]. It is therefore essential to find an accurate indicator of plant S status that is suitable as a reliable and relevant diagnostic tool under field conditions in order to evaluate the S requirements of B .…”
Section: Introductionmentioning
confidence: 99%
“…) in vacuole to sustain plant growth 25 . A constant decline of water resources, due to climate change, is one of the major threats to the future food security of ever increasing world population.…”
Section: mentioning
confidence: 99%
“…The P is crucial macronutrient at the early stage of plant growth and development as it is required for maintaining the various processes within the plant. Similarly, the S also plays an important role in plant growth because of its involvement in the production of various metabolites such as amino acids, proteins, sulpho-lipids and production of chlorophyll (Sorin et al, 2015). …”
Section: Introductionmentioning
confidence: 99%